Analisis Strategi Perencanaan Konten Media Sosial Instagram Yayasan Kesehatan Telkom melalui Model SoMe - Aulia Hermiati Putri; Muhammad Al Assad Rohimakumullah (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
Public relations in a company need to utilize social media properly so that the benefits can be felt by both the company and the target audience. The use of social media requires a content planning strategy on social media so that the messages presented in the content are conveyed to the target audience optimally. The purpose of this research is to find out how the content planning strategy on the Telkom Health Foundation's social media. The research method used is qualitative. Data and information that can support this research are collected through in-depth interviews, direct observation of content published on Instagram social media, and Instagram content analysis. This research discusses the relationship between Yakes Telkom's Instagram social media content planning strategy and The Circular Model of SoMe. This research proves that the model is not suitable for content planning strategies on health social media because it requires additional aspects regarding appropriate references and sources.